Signatures of dark matter in cosmic-ray observations. (February 2020) - Cuoco, Alessandro
Abstract: I provide a short review of the current status of indirect dark matter searches with gamma rays, charged cosmic rays and neutrinos. For each case I will focus on various excesses reported in the literature which have been interpreted as possible hints of dark matter, and I will use them as examples to discuss theoretical aspects and analysis methodologies.